Manajemen pembelajaran berbasis ekologi pada pendidikan anak usia dini - Arneta Tasya; Dian Rahadian; Iman Nasrulloh (Curricula: Journal of Curriculum Development, 2026)
The growing attention to environmental education in early childhood has not been fully balanced by studies that integrate learning management aspects, underscoring the need for this research. This study aims to examine the development of research on ecology-based learning management in early childhood education through a Systematic Literature Review. The review identifies thematic trends, research patterns, and potential areas for development in this field. Data were collected via article searches in the Scopus database using the Publish or Perish application, covering the period from 2020 to 2026. The selection process was conducted on the Covidence platform, while the bibliometric analysis was conducted in VOSviewer. The results show that research continues to focus on learning aspects, the role of educators, and children’s learning experiences. Keyword mapping places education, learning, and teachers as central themes. These findings indicate that the integration of ecology-based learning management remains limited and requires further systematic, comprehensive, and sustainable development.